Efektivitas Pemasaran Tabungan Emas dalam Meningkatkan Minat Berinvestasi Nasabah di Pegadaian Unit Pembantu Cabang Pemogan - Dian Erfiana; Ni Luh Putu Sariani (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
Pegadaian Gold Savings is a gold balance depository service that facilitates public gold investment, as well as a gold savings product that makes gold investment simple, safe, affordable and reliable. The purpose of this service activity is to increase customer interest in investing in the UPC Pemogan Pawnshop. The method used is observation and evaluation. The results of this activity indicate that the marketing strategy for Gold Savings at UPC Pemogan Pawnshop uses a marketing mix strategy, namely product, price, location, and promotion. Promotions are used with brochures, personal selling, sales promotions by giving free administration fees, and advertisements on Pawnshop TV. The most effective promotion strategy is personal selling. The advice that the author can convey to Pegadaian UPC Pemogan is to provide special sales for Gold Savings products so that it is easier to market Gold Savings products.